Pengaruh Penerimaan dan Gaya Hidup terhadap Perilaku Keuangan Mahasiswa UKI Paulus - Stenly Dhio Salembe; Andryanus Paridy; Benyamin Mongan (Politeknik Kampar, 2025)
This study examines the impact of acceptance and lifestyle on the financial behavior of UKIP students. The research employs a quantitative approach with regression analysis. The findings indicate that acceptance does not significantly influence students' financial behavior. In other words, income level does not directly determine how students manage their finances. Other factors, such as financial literacy and money management habits, may have a more substantial role in shaping financial behavior. Therefore, financial education and proper financial planning are essential. On the other hand, lifestyle has a positive and significant effect on students' financial behavior. The better the lifestyle adopted, the more effectively students manage their expenses and fulfill financial obligations. To maintain financial well-being, students should cultivate a responsible financial lifestyle by minimizing unnecessary expenditures, creating realistic budgets, and enhancing awareness of the importance of savings and investments for the future.